Novel alkylaminoethyl derivatives of androstane 3-oximes as anticancer candidates: synthesis and evaluation of cytotoxic effects - Ajduković, Jovana J; Jakimov, Dimitar S; Rárová, Lucie; Strnad, Miroslav; Dzichenka, Yaraslau U; Usanov, Sergey; Škorić, Dušan Đ; Jovanović-Šanta, Suzana S; Sakač, Marija N (RSC advances, 2021)
Steroid anticancer drugs are the focus of numerous scientific research efforts. Due to their high cytotoxic effects against tumor cells, some natural or synthetic steroid compounds seem to be promising for the treatment of different classes of cancer. In the present study, fourteen novel O-alkylated oxyimino androst-4-ene derivatives were synthesized from isomerically pure 3E-oximes, using different alkylaminoethyl chlorides. Their in vitro cytotoxic activity was evaluated against eight human cancer cell lines, as well as against normal fetal lung (MRC-5) and human foreskin (BJ) fibroblasts, to test the efficiency and selectivity of the compounds. Most derivatives displayed strong activity against malignant melanoma (G-361), lung adenocarcinoma (A549) and colon adenocarcinoma (HT-29) cell lines. Angiogenesis was assessed in vitro using migration scratch and tube formation assays on HUVEC cells, where partial inhibition of endothelial cell migration was observed for the 17α-(pyridin-2-yl)methyl 2-(morpholin-4-yl)ethyl derivative. Among the compounds that most impaired the growth of lung cancer A549 cells, the (17E)-(pyridin-2-yl)methylidene derivative bearing a 2-(pyrrolidin-1-yl)ethyl substituent induced significant apoptosis in these cells. In combination with low cytotoxicity toward normal MRC-5 cells, this molecule stands out as a good candidate for further anticancer studies. In addition, in vitro investigations against cytochrome P450 enzymes revealed that certain compounds can bind selectively in the active sites of human steroid hydroxylases CYP7, CYP17A1, CYP19A1 or CYP21A2, which could be important for the development of novel activity modulators of these enzymes and identification of possible side effects.